High Temperature Unfolding Simulations of a Single-stranded DNA i-Motif - Smiatek, Jens; Liu, Dongsheng; Heuer, Andreas (Current Physical Chemistry, 2012)
We present the results of high temperature 500 K Molecular Dynamics simulations of a single-stranded DNA i-motif. The unfolding pathways are compared to a biased metadynamics simulation at 300 K. Our results indicate a remarkable agreement between the trajectories. We found that the unfolding process can be described by two main mechanisms with a small number of eigenvectors.
Keywords: applied methods